Nutrition Education in College Students Using Diffusion of Innovation Theory: An Interventional Study - Gunika Sehgal; Swati Jain (Preventive Medicine: Research & Reviews, 2024)
Objective: To determine the consumption of nuts and oilseeds in college students and to enhance their awareness to improve the consumption through a nutrition education programme. Materials and Methods: An interventional study amongst the students of a college at the University of Delhi with the use of Diffusion of Innovation Theory. Results: There was a low consumption (<5 g/day) of nuts and oilseeds amongst 46% of participants with only 2.4% meeting the recommended intake (>30 g/day). Post-intervention, knowledge, attitude and most of the practices significantly improved (P < 0.05), with 11.3% consuming >30 g/day. Participants reached the decision phase of Diffusion of Innovation Theory favouring adoption, but only a few were implementing the recommended changes. Conclusion: There is a need to improve awareness and practice about nuts and oilseeds consumption in young college students.